1983
DOI: 10.1007/bf02405084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogens and phosphorus depletion on plasma calcitonin in the rat

Abstract: Summary.To investigate interactions between estrogens and calcitonin (CT), we have studied the effect of oophorectomy and estrogen replacement on plasma CT in female rats in response to an acute intravenous calcium stimulus and to hypercalcemia induced by dietary phosphorus deprivation.Plasma CT 5 min after an intravenous calcium stimulus (10 mg Ca/kg) was 176 • 11 pg/ml (mean • SEM) in rats subjected to oophorectomy compared with 244 • 15 pg/ml in sham-operated control rats (P < .001). Administration of estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…These results suggest that estrogen has a positive effect on C cell secretory activity. Other studies also confirmed that ovariectomized animals have diminished basal CT secretion and that estrogen supplement therapy throughout the period of estrogen deficiency prevents a reduction of CT secretion (Catherwood et al 1983;Yamazaki and Kinoshita 1986;Grauer et al 1993). Moreover, Greenberg et al (1986) showed that 17b estradiol promptly stimulated CT secretion from rat thyroid glands in vitro in a dose-related manner.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These results suggest that estrogen has a positive effect on C cell secretory activity. Other studies also confirmed that ovariectomized animals have diminished basal CT secretion and that estrogen supplement therapy throughout the period of estrogen deficiency prevents a reduction of CT secretion (Catherwood et al 1983;Yamazaki and Kinoshita 1986;Grauer et al 1993). Moreover, Greenberg et al (1986) showed that 17b estradiol promptly stimulated CT secretion from rat thyroid glands in vitro in a dose-related manner.…”
Section: Discussionmentioning
confidence: 65%
“…On the contrary, morphometric data and subcellular organization of C cells in castrated pigs suggested stimulation of specific protein synthesis (Sekulić and Lovren 1995). Nevertheless, estrogen treatment of ovariectomized (Ovx) rats and women was found to have a stimulatory effect on secretion of CT (Catherwood et al 1983;Yamazaki and Kinoshita 1986;Isaia et al 1992;Grauer et al 1993). However, other authors showed no effect of estrogen replacement therapy (Selby and Peacock 1986) or inducement of a slight reduction in basal CT levels in postmenopausal women (Body 1993).…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, several studies have shown that estrogen treatment stimulates CT secretion in Ovx rats (Catherwood et al. ; Filipović et al. ) and women (Isaia et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have shown that the circulating concentrations of CT are decreased in the oophorectomized or postmenopausal state (Milhaud et al, 1978), and that estrogen increases CT secretion (Morimoto et al, 1980). In oophorectomized rats, the plasma CT response to a calcium challenge is impaired and can be restored to normal levels by estrogen replacement therapy (Catherwood et al, 1983). Rat pup thyroid incubation studies demonstrate that estradiol can stimulate CT secretion in vitro (Greenberg et al, 1986).…”
Section: Introductionmentioning
confidence: 99%